Spatial Attenuation of the Growth-Poverty Nexus: A Spatial Econometric Analysis Across Regencies in West Java, Indonesia - Selin Sanita; Mia Riskika; Rika Miswardiya Ningsih; Hipzi Aulia Khair (Journal of Economics Business Industry, 2024)
The persistent decoupling of aggregate economic growth from subnational poverty reduction constitutes one of the most consequential paradoxes in development economics, particularly in spatially polarised economies where productive activity and welfare gains accumulate in core regions while peripheral areas remain structurally excluded. This study investigates the transmission mechanisms through which three structural determinants Gross Regional Domestic Product (GRDP), average years of schooling as a human capital proxy, and the Gender Empowerment Index (GEI) shape poverty outcomes across five chronically poor regencies in West Java, Indonesia: Indramayu, Tasikmalaya, Garut, Cianjur, and Kuningan, over the period 2010–2021. Employing a balanced panel dataset of 60 observations drawn from the Central Bureau of Statistics, the study applies multiple linear regression within a Fixed Effect Model (FEM) framework, selected through sequential Chow and Hausman tests, with all classical diagnostic criteria satisfied. Estimation results reveal that GRDP exerts a negative and statistically significant effect on poverty (β = −0.487; p < 0.01), yet with a modest coefficient magnitude that reflects attenuated trickle-down effects arising from growth concentration in West Java's northern manufacturing corridor. Education demonstrates the largest poverty-reducing effect in the model (β = −1.624; p < 0.01), consistent with a pronounced human capital scarcity premium in regencies where average schooling remains below eight years. The GEI, by contrast, yields no significant effect (β = −0.032; p = 0.508), revealing a critical transmission failure between nominal empowerment gains and substantive welfare improvements attributable to the double burden of domestic and productive labour, the prevalence of unpaid family work, and entrenched patriarchal norms in Sundanese agrarian communities. Jointly, the three variables account for 92.6 percent of poverty variation (Adjusted R² = 0.926). This study advances the subnational poverty literature by delivering spatially specific panel evidence from Indonesia's most populous yet empirically understudied province, while enriching the feminisation of poverty framework within a distinctive cultural context that challenges the universality of gender-empowerment-to-welfare transmission pathways